Mebendazole vs. mebendazole-pyrantel pamoate for soil-transmitted helminthiasis infection in children - Fereza Amelia; Muhammad Ali; Syahril Pasaribu (Indonesian Pediatric Society, 2013)
AbstractBackground Soil-transmitted helminthiasis (STH) is the mostcommon infection in developing countries. Although it causeshigh morbidity, it is still difficult to find the efficacy dose ofantihelmintics for its treatment.Objective To determine the efficacy ofmebendazole and mebendazole-pyrantel pamoate in treating STH infection in children.Methods We conducted a randomized open-label controlled trialfrom July to September 2009 in Secanggang, Langkat District,North Sumatera Province, Indonesia, on primary school-agedchildren. Before the intervention, data on age, sex, nutritionalstatus, and STH infection status were collected. The childrenwere randomized into two groups. Children in group I received asingle dose of 500 mgmebendazole while they in group II receiveda single dose of 500 mg of mebendazole combined with 10 mg/kgBW of pyrantel pamoate. We examined subjects' stool specimenson days 7, 14, 21, and 28 after treatment to determine cure ratesand egg reductions. Statistical analyses were performed by Chisquare and student's Ttest with 95% confidence intervals and Pvalues of< 0.05 considered to be significant.Results We found that the cure rates were 95.4%, 78.5%, and893%for Ascaris lumbricoides, Trichuris trichiura, and mixed (A lumbricoidesand T trichiura) infections, respectively, in the mebendazole group.The cure rates were 98.5%, 89.2%, and 90.2% for A lumbricoides,T trichiura, and mixed infections, respectively, in the mebendazolepyrantelpamoate group. Although the cure rate results were notsignificantly different between the 2 treatment groups, the total eggsper gram (EPG) was significantly lower for both A lumbricoides andT trichiura infections (P=0.001 and P=0.002, respectively) in thecombination therapy group than in the mebendazole alone group.Conclusion Mebendazole in combination with pyrantel pamoatehas higher efficacy than mebendazole alone in terms of faster eggreduction rates. However, the cure rates of these two antihelminticsregimens are similar.